(untitled) (Journal of Advances and Scholarly Researches in Allied Education, 2023)
Custodial torture, police abuses and prolonged pre-trial detention remain pressing global human-rights concerns that erode the rule of law, undermine fair trial guarantees and damage public trust in criminal justice institutions. This article examines legal and institutional safeguards developed at international and national levels to prevent, detect and remedy custodial abuses, and to reduce unnecessary pre-trial detention. It traces the historical evolution of norms and jurisprudence; analyses key instruments and standards such as the International Covenant on Civil and Political Rights (ICCPR), the Convention Against Torture (CAT), the Body of Principles on detention, the Tokyo Rules, the Nelson Mandela Rules and monitoring mechanisms such as the Optional Protocol to CAT (OPCAT); and reviews landmark jurisprudence and reform efforts (notably D.K. Basu in India and police-reform directions like Prakash Singh). The paper also presents comparative international perspectives, highlights implementation gaps, and offers conclusions and future directions for policy, law and practice aimed at eliminating torture and limiting pre-trial detention to what is strictly necessary.